Quality of Antiepileptic Treatment Among Older Medicare Beneficiaries With Epilepsy: A Retrospective Claims Data Analysis. Issue 7 (July 2017) - Pisu, Maria; Richman, Joshua; Piper, Kendra; Martin, Roy; Funkhouser, Ellen; Dai, Chen; Juarez, Lucia; Szaflarski, Jerzy P.; Faught, Edward
Abstract : Background: Enzyme-inducing antiepileptic drugs (EI-AEDs) are not recommended for older adults with epilepsy. Quality Indicator for Epilepsy Treatment 9 (QUIET-9) states that new patients should not receive EI-AEDs as first line of treatment. In light of reported racial/ethnic disparities in epilepsy care, we investigated EI-AED use and QUIET-9 concordance across major racial/ethnic groups of Medicare beneficiaries. Research Design: Retrospective analyses of 2008–2010 Medicare claims for a 5% random sample of beneficiaries 67 years old and above in 2009 augmented for minority representation. Logistic regressions examined QUIET-9 concordance differences by race/ethnicity adjusting for individual, socioeconomic, and geography factors. Subjects: Epilepsy prevalent (≥1 International Classification of Disease-version 9 code 345.x or ≥2 International Classification of Disease-version 9 code 780.3x, ≥1 AED), and new (same as prevalent+no seizure/epilepsy events nor AEDs in 365 d before index event) cases. Measures: Use of EI-AEDs and QUIET-9 concordance (no EI-AEDs for the first 2 AEDs). Results: Cases were 21% white, 58% African American, 12% Hispanic, 6% Asian, 2% American Indian/Alaskan Native. About 65% of prevalent, 43.6% of new cases, used EI-AEDs. QUIET-9 concordance was found for 71% Asian, 65% white, 61% Hispanic, 57% African American, 55% American Indian/Alaskan new cases: racial/ethnic differences were not significant in adjusted model. Beneficiaries without neurology care, in deductible drug benefit phase, or in high poverty areas were less likely to have QUIET-9 concordant care. Conclusions: EI-AED use is high, and concordance with recommendations low, among all racial/ethnic groups of older adults with epilepsy. Potential socioeconomic disparities and drug coverage plans may affect treatment quality and opportunities to live well with epilepsy.